Principles of Islamic Communication and their Relevance in Character Formation of Students: A Study of Surah An-Nahl 125 Tafsir At-Thabari's Perspective - Muhammad Hatta; Ismailinar Ismailinar; Alhuda Alhuda; Muhammad Syahrial Razali Ibrahim (Electronic Journal of Education, Social Economics and Technology, 2025)
This article examines the principles of Islamic communication contained in Surah An-Nahl verse 125, which contains three main concepts: hikmah (wisdom), mau'izah hasanah (good advice), and jadal (good debate). These three principles have deep relevance in the context of character education, especially in shaping the noble morals of students. Using an interpretive qualitative descriptive method, this study analyzes At-Thabari's interpretation of the verse, as well as its application in character education. The results of the study show that the application of Islamic communication principles in the interaction between educators and students can create an environment that supports the formation of strong characters, noble character, and able to adapt well in society. This article also reviews how Islamic communication plays an important role in developing students' morals and ethics, making it an effective tool in achieving the goal of better character education.